Poésie et francophonie - Léopold Sédar Senghor; Serge Bourjea (Continents manuscrits)
In this interview conducted in 1985 by Serge Bourjea, then assistant professor at the university of Dakar, Léopold Sédar Senghor, recently elected member of the Académie française, reflects on the future of the French language, and more specifically on how its opening up to the Francophonie constitutes a major challenge for its vitality. This is an opportunity for the poet-president to look back at his various sources of inspiration, drawn both from the European literary tradition and from what he called “the school of traditional Negro-African poetry”, and to show just how essential this cross-fertilization is to his poetic writing. The two agrégés do not shy away from the puzzling question of the status and future of the French language in ex-colonized countries, which does not prevent Senghor from setting out the reasons why he sees it as the possible language of the civilization of the Universal.